Characterization and Genomic Analysis of SFPH2, a Novel T7virus Infecting Shigella - Yang, Chaojie; Wang, Haiying; Ma, Hui; Bao, Renlong; Liu, Hongbo; Yang, Lang; Liang, Beibei; Jia, Leili; Xie, Jing; Xiang, Ying; Dong, Nian; Qiu, Shaofu; et al. (Frontiers in Microbiology, 2018)
Shigellosis, caused by Shigella, is a major global health concern, with nearly 164.7 million cases and over a million deaths occurring annually worldwide. Shigella ﬂexneri is one of the most common subgroups of Shigella with a high incidence of multidrug-resistance. The phage therapy approach is an effective method for controlling multidrug-resistant bacteria. However, only a few Shigella phages have been described to date. In this study, a novel lytic bacteriophage SFPH2 was isolated from a sewage sample obtained from a hospital in Beijing, China, using a multidrug-resistant Shigella ﬂexneri 2a strain (SF2) isolated from the fecal sample of a dysentery patient. SFPH2 is a member of the Podoviridae virus family with an icosahedral capsid and a short, non-contractile tail. It was found to be stable over a wide range of temperatures (4 – 50°C) and pH values (pH 3 – 11). Moreover, SFPH2 could infect two other S. ﬂexneri serotypes (serotypes 2 variant and Y). High-throughput sequencing revealed that SFPH2 has a linear double-stranded DNA genome of 40,387 bp with 50 open reading frames. No tRNA genes were identified in the genome. Comparative analysis of the genome revealed that the SFPH2 belongs to the subfamily Autographivirinae and genus T7virus. The genome shows high similarity with other enterobacterial T7virus bacteriophages such as Citrobacter phage SH4 (95% identity and 89% coverage) and Cronobacter phage Dev2 (94% identity and 92% coverage). A comparison of the fiber proteins showed that minor differences in the amino acid residues might specify different protein binding regions and determine host species. In conclusion, this is the first report of a T7virus that can infect Shigella; SFPH2 has a functional stability under a wide range of temperatures and pH values, showing the potential to be widely applied to control Shigella–associated clinical infections and reduce the transmission rates of S. flexneri serotype 2a and its variants in the environment.